In vitro selection and characterization of buffelgrass somaclones with different responses to water stress - Carloni, Edgardo José; Tommasino, Exequiel Arturo; Lopez Colomba, Eliana; Ribotta, Andrea Noemi; Quiroga, Mariana Paola; Griffa, Sabrina Mariana; Grunberg, Karina (2018)
Buffelgrass is a forage grass that reproduces mainly by apomixis. In species with this reproduction mode, in vitro selection allows the incorporation of alternatives in a breeding program. The aims were to define a protocol for in vitro selection, provide a molecular and morphological characterization of the progenies of regenerated plants, and evaluate them under water stress conditions. In the embryogenic callus induction medium (IM), the highest values of the variables fresh weight of embryogenic calli, proportion of embryogenic calli and number of regenerated seedlings (NRS) were obtained in the 25 mM mannitol treatment. The remaining concentrations of the osmotic agent (50, 75, 100 and 150 mM) had a negative effect on these variables. In the regeneration medium (RM), NRS was reduced at all mannitol concentrations. When embryogenic calli were induced and seedlings were regenerated maintaining mannitol concentrations in IM and RM, the highest NRS values were recorded at 25 mM mannitol. In vitro regenerated seedlings transplanted to an experimental plot exhibited different morphological characteristics from those of the anther donor plant. ISSR primers detected 22% of polymorphic bands and divergence between 0.20 and 0.37 in in vitro regenerated plants. Finally, water stress assays confirmed that S1 progenies exhibited a differential behavior from that of the parent material. Under 100 mM of mannitol used as selection pressure in IM or in both IM and RM, S1 progenies of two regenerated materials had higher height, fresh weight and dry weight at the end of water stress assay.